Projecting neurons from the lateral entorhinal cortex to the basolateral amygdala mediate the encoding of incidental odor–taste associations - Jose Antonio González-Parra; Vittoria Acciai; Laura Vidal-Palencia; Marc Canela-Grimau; Arnau Busquets-Garcia (Proceedings of the National Academy of Sciences, 2025)
Since our first steps in life, we are forming incidental associations between diverse stimuli across various sensory modalities that influence our future choices and facilitate adaptation to environmental fluctuations. Daily behavior is usually governed by indirect incidental associations among sensory cues that have never been explicitly paired with a reinforcer. This phenomenon, known as higher-order conditioning, can be systematically investigated in laboratory animals through specific behavioral paradigms such as sensory preconditioning protocols. In this study, using “Targeted Recombination in Active Populations” (TRAP2) transgenic mice, we have interrogated which are the brain areas orchestrating the encoding of associations between olfactory and gustatory stimuli and the expression of an aversive odor–taste sensory preconditioning paradigm. We identified neuronal ensembles within the basolateral amygdala specifically activated during odor–taste associations. To demonstrate the causal involvement of this brain region in our sensory preconditioning task, we inhibited it during the preconditioning phase (i.e., incidental associations) using a chemogenetic approach, which caused a clear impairment of the mediated responses. In addition, using retrograde tracers in the basolateral amygdala of TRAP2 mice, we observed that the projections from the lateral entorhinal cortex to the basolateral amygdala are particularly activated during odor–taste associations. Notably, the chemogenetic inhibition of this brain circuit impaired the mediated aversion performance in our sensory preconditioning task. Overall, these findings highlight the amygdala as a pivotal modulator of incidental associations during an aversive sensory preconditioning task and point toward a brain circuit crucially involved in these complex cognitive processes.